Crisis response vs crisis cluster: a test of situational crisis communication theory on two crisis clusters in Indonesian public relations - Kriyantono, Rachmat; Mckenna, Bernard (Penerbit Universiti Kebangsaan Malaysia, 2019)
Situational crisis communication theory (SCCT) is applied in this research to evaluate Air Asia crisis responses. The research tests whether crisis responses are consistent with the SCCT premise related to situation when a crisis has more than one cluster. SCCT argues that in this case, organisation’s crisis response strategy is adjusted according to the crisis clusters. The crisis manager can use a defensive strategy for victim cluster and an accommodative strategy when the company has intentional cluster. From the premise, the researchers formulates a proposition: because of having two crisis clusters (victim and intentional clusters), the crisis response strategies of Air Asia are defensive and accommodative. This study analyses both news and press releases on the selected crisis. The content analysis of media news reveals that the company has both intentional and victim clusters, although the intentional cluster is reported more frequently. Content analysis of the company’s press releases identifies that the response strategies are accommodative and bolstering instead of accommodative and defensive. Accommodative strategy is used because most public attributions appeared to be intentional, while a defensive strategy is not applied because the media rarely reported the event as victim cluster. As a result, the company were able to successfully deal with the crisis. It can be concluded that a company with two crisis clusters should choose the relevant crisis response strategy in accordance with the type of the cluster in the public domain.